2018
DOI: 10.32877/bt.v1i2.41
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Lecturer Teaching Performance Using AHP and SAW Methods

Abstract: The lecturer performance evaluation activity is the routine of an university in continuously improving internal quality as an evaluation and development of educational institutions. Buddhi Dharma University Tangerang, every semester evaluates lecturers' performance. But the results obtained are not optimal, this is due to the absence of an effective and efficient method in determining the results, especially in the Faculty of Science and Technology, Information System Departement. The assessment process is car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 3 publications
0
9
0
3
Order By: Relevance
“…This study aims to analyze the results of the questionnaire, calculated by combining the Analytical Hierarchy Process (AHP) method for weighting and combined the Simple Addictive Weighting (SAW) method for ranking. The results obtained were the level of criteria weighting accuracy reached 90.39% with 28 lecturers which teaching 47 subjects in the Information Systems Departement [3]. The second journal Designing Decision Making System for Giving Approval to home loan Credit is a financial facility that allows a person or business entity to borrow money to buy a product and repay it within a specified period of time.…”
Section: In the Journal Evaluation Of Lecturer Teaching Performance Using Ahp And Saw Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study aims to analyze the results of the questionnaire, calculated by combining the Analytical Hierarchy Process (AHP) method for weighting and combined the Simple Addictive Weighting (SAW) method for ranking. The results obtained were the level of criteria weighting accuracy reached 90.39% with 28 lecturers which teaching 47 subjects in the Information Systems Departement [3]. The second journal Designing Decision Making System for Giving Approval to home loan Credit is a financial facility that allows a person or business entity to borrow money to buy a product and repay it within a specified period of time.…”
Section: In the Journal Evaluation Of Lecturer Teaching Performance Using Ahp And Saw Methodsmentioning
confidence: 99%
“…Also for consideration, the registration file that will be used for decision-making support and the registration file often contains incorrect data on prospective debtors. Because of that consideration, the system and the application will be created using the AHP and SAW methods [3]. AHP and SAW method was chosen because this method determines the weight value of each attribute, then proceed with a ranking process that will select the best alternative from a number of all alternatives.…”
Section: Informationmentioning
confidence: 99%
“…In the Daniawan journal, that evaluating lecturers' performance in teaching using the AHP and SAW methods can provide a level of consistency 96.75% from the 10 assessment indicators of 28 lecturers teaching 47 courses. By combining these two methods will be able to provide more accurate results and it is very unlikely the lecturers will have the same rating ranking [6].…”
Section: Literatures Reviewmentioning
confidence: 99%
“…The results showed that the standard weighted accuracy rate of 28 lecturers reached 90.39%, which greatly improved the efficiency of evaluation analysis while ensuring the accuracy rate. 5 Goyal et al proposed an optimization model based on Fuzzy Analytic Hierarchy Process (FAHP) for nonlinear problems, and solved the problem of inconsistent weights with a new constraint condition. Finally, it was compared with other optimization models, and it was found that this model has better consistency weight for multi criteria decision-making system.…”
Section: Introductionmentioning
confidence: 99%